Pengembangan Lembar Kegiatan Siswa (LKS) Berdasarkan Model Pembelajaran Guided Discovery - Christina Eva Nuryani; Anggi Meylia Saraswati (Universitas PGRI Semarang, 2018)
This research aims to produce student’s worksheet based on guide discovery learning model School that quality based on aspect validity, practically, and effectivity.This Reseach take place in 15 Junior High School of Yogyakarta at 2017/2018. This are research and development. Research and development design by development procedural of ADDIE ( Analysis, Design, Development, Implementation, and Evaluation). This research based on problems that are teacher still use uninterested teaching material and text book from goverment is not easy to understand by student. The result of development show that analysis phase we get curriculum,necessity, and material analize. Design phase get draft LKS and validity assessment paper. Development phase to develop draft LKS and validity assessment. Implementation phase to use LKS in learning, observ the learning, and test. Evaluation to analize practically and effectivity of LKS. The result of research show that student’s worksheet has complied criteria valid, practice, and effective. Student’s worksheet declare to be valid based on expert and teacher’s assessment with score 3,37 that category is ”very valid”. Student’s worksheet declare to be practice based on teacher and student quisioner with score 3,63 that category is ”practice”. Student’s worksheet declare to be effective based on post test with pass percentage of the result test score 94,11% that category is ”effective”. The conclude is student’s worksheet that develop is good to use in learning.